2018
DOI: 10.1039/c8ra00921j
|View full text |Cite
|
Sign up to set email alerts
|

Effects of anions on the underpotential deposition behavior of Cu on polycrystalline Pt

Abstract: Effects of anions on underpotential deposition behavior of Cu at polycrystalline Pt has been investigated by cyclic voltammetry, chronoamperometry and electrochemical impedance spectroscopy techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…form an adsorbed coating on the gold or platinum electrode surface. [49] All the above-mentioned charge storing mechanisms often operates simultaneously, depending on the nature of electrode and electrolyte materials employed during the device fabrication. [50] Similarly, it has been observed that certain redox-active materials such as LiCoO 2 , MoO 2 , NiMoO 4 , etc.…”
Section: Ni(ohmentioning
confidence: 99%
See 1 more Smart Citation
“…form an adsorbed coating on the gold or platinum electrode surface. [49] All the above-mentioned charge storing mechanisms often operates simultaneously, depending on the nature of electrode and electrolyte materials employed during the device fabrication. [50] Similarly, it has been observed that certain redox-active materials such as LiCoO 2 , MoO 2 , NiMoO 4 , etc.…”
Section: Ni(ohmentioning
confidence: 99%
“…Such behavior is observed when metal ions like ‐ Cu 2+ , Pb 2+ , Hg 2+ , etc. form an adsorbed coating on the gold or platinum electrode surface [49] . All the above‐mentioned charge storing mechanisms often operates simultaneously, depending on the nature of electrode and electrolyte materials employed during the device fabrication [50] …”
Section: Introductionmentioning
confidence: 99%
“…Due to their excellent charge storage capacity, inherent exibility for exible electronic devices, large potential window between 1 and +1 V, simple synthesis process, and low cost, conductive polymers, such as polypyrrole and polyaniline, have been extensively researched for supercapacitor applications. 4,64,98 However, during the insertion/extraction process, conducting polymers experience both swelling and shrinkage, which reduce the mechanical stability of the electrodes, and consequently the cycling stability of supercapacitors. In addition to conducting polymers, many transition metal compounds with greater electrochemical stability than polymerbased materials and higher capacitance than carbon-based materials have been studied for supercapacitor applications.…”
Section: Materials For Scsmentioning
confidence: 99%